Financial Deepening Relationship with Economic Growth in Indonesia - Putri, Novarinda Vanny Kusuma; Mubin, Muhammad Khoirul (Jurnal Ilmu Ekonomi Terapan, 2021)
This article aims to analyze the interaction between financial deepening and economic growth in Indonesia. In this case, it also indirectly analyzes the interaction between the research control variables, namely the interbank money market interest rate and the exchange rate with economic growth in Indonesia. The journal uses secondary data, including taking from the official website of the Central Bureau of Statistics and Bank Indonesia, which is the website of the Republic of Indonesia government. This journal uses an analysis of the interaction between variables in the period 2010-2019. The method used is the VECM method, a method used to explore financing and exchange rates which have a significant negative interaction with economic growth in Indonesia. And the interbank money market interest rate has a significant negative interaction with economic growth in Indonesia. In addition, the financial interior also has directional interactions with the government in Indonesia so that it can be said to follow bidirectional causality. Keywords: Financial Deepening, Economic Growth, VRCM, Bidirectional Causality JEL : G320, C320